The determinants of household’s bank switching - Brunetti, M.; Ciciretti, R.; Djordjevic, Lj. (Journal of Financial Stability, 2016)
We investigate households’ bank switching exploiting a unique representative dataset from Bank of Italy Survey on Household Income and Wealth that follows the households and their bank(s) over time. First, we document that bank switching is quite prevalent in our sample, with almost a quarter of households changing their main bank in a biannual horizon. Next, we relate the decision to switch to the features and dynamics of household bank relationship, and to the characteristics of both households and banks. In line with the switching cost theory, we find that using more than a single bank, as well as the intensity (number of services used), and the scope (bank services used) of the relationship with the main bank play a role in shaping the households’ decision to switch. Moreover, bank switching is strongly and positively correlated with both taking out and having paid off a mortgage.